How connected are people with schizophrenia? Cell phone, computer, email, and social media use - Miller, Brian J.; Stewart, Adriana; Schrimsher, John; Peeples, Dale; Buckley, Peter F. (Psychiatry research, 2015)
Technologies such as Internet based social media network (SMN) websites are becoming an important part of many adult lives; however, less is known about their use in patients with schizophrenia. We need to determine (1) how “connected” are patients with schizophrenia?, (2) do these technologies interfere with the patient׳s illness?, and (3) do patients envision these technologies being involved in their treatment? We recruited 80 inpatients and outpatients age 18–70 with schizophrenia to complete a brief survey on the prevalence and frequency of cell phone, text messaging, computer, email, and SMN use, and associated attitudes. 56% of subjects use text messaging, 48% have an email account, and 27% of subjects use SMN sites daily, with Facebook being the most popular. Many current users agreed that these technologies help them interact/socialize more, expressed interest in receiving text messages from their doctors, and disagreed that these technologies make symptoms worse. These preliminary findings should be investigated in larger samples, but suggest that these technologies afford a unique opportunity to engage and improve treatment for some patients with schizophrenia. •Fifty-six percent of subjects use text messaging, 48% have an email account.•Twenty seven percent of subjects use social media sites daily (Facebook the most popular).•Many current users agreed that these technologies increase socialization.•Many patients are interested in mobile technologies playing a role in treatment.